KADAR PEROKSIDA LIPID DAN AKTIVITAS SUPEROKSIDA DISMUTASE SERUM DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 - KRISTINA, HENI; SARTONO, NURMASARI; RUSDI, RUSDI (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Prevalence of type 2 diabetes mellitus rapidly increase in industry and developing country. Oxidative stress was estimated has role in development of type 2 diabetes mellitus. This study was aim to measure levels of malondialdehyde (MDA) and activity of superoxide dismutase (SOD) in type 2 diabetes mellitus, and also to analyse the relationship among both. This study was conducted on July-October 2014, using Ex Post Facto method and cross sectional design. The result showed that MDA serum levels significantly higher in diabetes mellitus patient compare to normal (P=0,000). Activity of superoxide dismutase (SOD) in diabetes mellitus serum has no significant difference with normal (P=0,290).There was possitive correlation between levels of MDA and activity of SOD in type 2 diabetes mellitus but not significant (P=0,478) with rs=0,199, thus also in normal subject (P=0,194) with rs=0,355. There was no significant different between two correlation coefficient (P=0,6781). In conclusion, there was significant different level of MDA, there was no significant different activity of SOD, there was positive correlation but not significant between levels of MDA and activity of SOD serum in type 2 diabetes mellitus and normal. And there was no significant different between two correlation coefficient. Keywords: malondialdehyde, superoxide dismutase, type 2 diabetes mellitus